Against all odds: The road to success in the development of human immune reconstitution mice - Yixiao Bin; Jing Ren; Haowei Zhang; Tianjiao Zhang; Peijuan Liu; Zhiqian Xin; Haijiao Yang; Zhuan Feng; Zhinan Chen; Hai Zhang (Animal Models and Experimental Medicine, 2024)
Abstract The mouse genome has a high degree of homology with the human genome, and its physiological, biochemical, and developmental regulation mechanisms are similar to those of humans; therefore, mice are widely used as experimental animals. However, it is undeniable that interspecies differences between humans and mice can lead to experimental errors. The differences in the immune system have become an important factor limiting current immunological research. The application of immunodeficient mice provides a possible solution to these problems. By transplanting human immune cells or tissues, such as peripheral blood mononuclear cells or hematopoietic stem cells, into immunodeficient mice, a human immune system can be reconstituted in the mouse body, and the engrafted immune cells can elicit human‐specific immune responses. Researchers have been actively exploring the development and differentiation conditions of host recipient animals and grafts in order to achieve better immune reconstitution. Through genetic engineering methods, immunodeficient mice can be further modified to provide a favorable developmental and differentiation microenvironment for the grafts. From initially only being able to reconstruct single T lymphocyte lineages, it is now possible to reconstruct lymphoid and myeloid cells, providing important research tools for immunology‐related studies. In this review, we compare the differences in immune systems of humans and mice, describe the development history of human immune reconstitution from the perspectives of immunodeficient mice and grafts, and discuss the latest advances in enhancing the efficiency of human immune cell reconstitution, aiming to provide important references for immunological related researches.